2013
DOI: 10.3390/toxins5111948
|View full text |Cite
|
Sign up to set email alerts
|

Atractaspis aterrima Toxins: The First Insight into the Molecular Evolution of Venom in Side-Stabbers

Abstract: Although snake venoms have been the subject of intense research, primarily because of their tremendous potential as a bioresource for design and development of therapeutic compounds, some specific groups of snakes, such as the genus Atractaspis, have been completely neglected. To date only limited number of toxins, such as sarafotoxins have been well characterized from this lineage. In order to investigate the molecular diversity of venom from Atractaspis aterrima—the slender burrowing asp, we utilized a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The only other characterized toxin type from Atractaspis venom has been a hemorrhagic metalloprotease (Ovadia, 1987). Transcriptome sequencing has shown that toxin types present in the venom include peptides (three finger, AVIT, beta-defensin, c-type lectin, cystatin, sarafotoxin, waprin), nonenzymatic proteins (CRiSP, lipocalin, nerve growth factor) and enzymes (acetylcholinesterase, kallikrein-type serine protease, metalloprotease, phospholipase A2) (Terrat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The only other characterized toxin type from Atractaspis venom has been a hemorrhagic metalloprotease (Ovadia, 1987). Transcriptome sequencing has shown that toxin types present in the venom include peptides (three finger, AVIT, beta-defensin, c-type lectin, cystatin, sarafotoxin, waprin), nonenzymatic proteins (CRiSP, lipocalin, nerve growth factor) and enzymes (acetylcholinesterase, kallikrein-type serine protease, metalloprotease, phospholipase A2) (Terrat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[15,16,17,18,19,20,21,22,23,24,25,26]). The results of this study not only contribute to our understanding of the molecular evolution of Australian elapid snake venom, particularly the influence of feeding ecology on venom composition, but will also constitute a platform for biodiscovery.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the use of venoms for drug discovery is rapidly emerging, it is still mostly an unrealized prospect due to recurrent technical bottlenecks that represent venom exploration. The advent of -omic techniques [57] lead to an explosion of the number of toxin sequences known, which are available for biomedical and biotechnological exploitation [8]. High-throughput production of these highly biologically-relevant molecules using recombinant technologies is currently the major limiting step between sequencing and biological screening and represents nowadays a considerable challenge.…”
Section: Introductionmentioning
confidence: 99%